2015
DOI: 10.1523/jneurosci.0548-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Role for Egr3 in Nucleus Accumbens Cell Subtypes in Cocaine Action

Abstract: An imbalance in molecular signaling cascades and transcriptional regulation in nucleus accumbens (NAc) medium spiny neuron (MSN) subtypes, those enriched in dopamine D1 versus D2 receptors, is implicated in the behavioral responses to psychostimulants. To provide further insight into the molecular mechanisms occurring in MSN subtypes by cocaine, we examined the transcription factor early growth response 3 (Egr3). We evaluated Egr3 because it is a target of critical cocaine-mediated signaling pathways and becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
196
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(212 citation statements)
references
References 69 publications
15
196
1
Order By: Relevance
“…The NAc (from Bregma, anterior/posterior:+1.6, medial/lateral:+/− 1.5, dorsal/ventral: − 4.4) of D1-Cre mice was bilaterally injected with a cre-inducible, double inverted open (DIO)-reading frame adeno-associated virus (AAV) AAV2.5-Ef1a-DIO-Egr3-EYFP (UNC viral vector core) 22 or AAV2.5-Ef1a-DIO-EYFP and AAV2.5-hsyn-DIO-Egr3-miR-mCitrine or AAV2.5-hsyn-DIO-SS-miR-mCitrine. 22 For calcium imaging experiments, mice were co-injected with AAV2.9-flex-GCaMP6f (UPenn Vector Core) and AAV2.2-DIO-Egr3-miR-LacZ or AAV2.2-DIO-SS-miR-LacZ.…”
Section: Methodsmentioning
confidence: 99%
“…The NAc (from Bregma, anterior/posterior:+1.6, medial/lateral:+/− 1.5, dorsal/ventral: − 4.4) of D1-Cre mice was bilaterally injected with a cre-inducible, double inverted open (DIO)-reading frame adeno-associated virus (AAV) AAV2.5-Ef1a-DIO-Egr3-EYFP (UNC viral vector core) 22 or AAV2.5-Ef1a-DIO-EYFP and AAV2.5-hsyn-DIO-Egr3-miR-mCitrine or AAV2.5-hsyn-DIO-SS-miR-mCitrine. 22 For calcium imaging experiments, mice were co-injected with AAV2.9-flex-GCaMP6f (UPenn Vector Core) and AAV2.2-DIO-Egr3-miR-LacZ or AAV2.2-DIO-SS-miR-LacZ.…”
Section: Methodsmentioning
confidence: 99%
“…We then identified several putative RUNX2 gene targets based on DNA consensus binding sites (Supplemental Table S1). Following self-administration (two-way repeated-measures ANOVA, drug × session interaction effect, F 9,180 = 3.36, p < .001) (Figure 6B), ChIP assays revealed increased RUNX2 binding in cocaine-treated rats at promoter regions of several target genes that we and others have previously implicated in cocaine-induced plasticity (one-way ANOVA, F 7,29 = 3.087, p = .015) (33,43,62,63) (Figure 6C), including Egr3 ( t test, t 8 = 2.196, p = .029), Dnml1 ( t test, t 7 = 2.419, p = .046), and Smarca4 (gene for Brg1; t test, t 8 = 2.169, p = .031) but not Tgfbr1 ( t test, t 6 = 0.9585, p = .374). Importantly, HSV- wtSmurf1 reduced expression of RUNX2-mediated genes affected by cocaine ( Egr3 : t test, t 13 = 1.872, p = .042; Dnml1: t test, t 14 = 0.746, p = .468; Tgfbr1: t test, t 14 = 0.746, p = .468; Smarca4: t test, t 11 = 2.316, p = .041) (Figure 6D).…”
Section: Resultsmentioning
confidence: 72%
“…We focused on RUNX2 because of its known interactions with c-Fos and c-Jun, immediate early genes involved in cocaine plasticity (58,59), to cooperatively bind AP-1 binding sites (57), which are essential components of transcriptional events following cocaine exposure (55,60,61). We found that SMAD1/5 and RUNX2 are upregulated in the NAc during withdrawal following cocaine self-administration, which prompted us to examine RUNX2 binding to target genes previously implicated in cocaine plasticity [i.e., Egr3 , Dnm1 , and Smarca4 (33,62,63)]. We found that cocaine self-administration induces enhanced RUNX2 binding at AP-1 sites along the promoters of these genes, suggesting that RUNX2 may be a master regulator of multiple pathways that govern cocaine-induced plasticity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, these methods allow analysis of the 'translatome'-ribosome-associated mRNA-which may be particularly sensitive to eventdependent regulation of protein translation. For example, RiboTag-expressing transgenic mice were recently used to compare differential gene expression responses to cocaine in striatal neurons expressing D 1 and D 2 dopamine receptors (Chandra et al, 2015).…”
Section: Ribotag: Not Lost In Translationmentioning
confidence: 99%